Monitoring of Official Degree Qualifications: The Key Role of Academic Quality Assurance Systems (AQAS) (2012)
The purpose of this article is focused on the development of a protocol designed to facilitate the monitoring process of the official degrees of a Spanish university. In response to the criteria and guidelines established in the Royal Decree 1393/2007, this proposal seeks to make available to the focus groups a useful and flexible tool, tailored to the different existing regulations, which assesses progress in the development of the curriculum, ensures the effective implementation of the degrees, and publishes the information available, relevant and appropriate. It also helps to identify weaknesses, potential improvements and best practices for dissemination. All this, with the ultimate aim of assuring the accreditation of Official Degrees. The monitoring protocol articulates the assessment, as a Check-List, in fulfillment of an annual series of indicators set out in the Academic Quality Assurance Systems (AQAS) included in the Proceedings of Degrees. Finally, the monitoring of new degrees comes up as a result of adaptation to the requirements of the European Higher Education Area.